Role of Neutrophil Extracellular Traps Regarding Patients at Risk of Increased Disease Activity and Cardiovascular Comorbidity in Systemic Lupus Erythematosus - Moore, Stanley (J Rheumatol, 2019)
OBJECTIVE. Neutrophil extracellular traps (NET) are essential in host defense, but are also linked to inflammation and autoimmunity, including in systemic lupus erythematosus (SLE). We recently described that immune complexes (IC) induce NET formation, promoting SLE-like disease in mice. In the current study, we investigated, for the first time to our knowledge, the role of NET in human SLE and their association with disease activity and severity. METHODS. Levels of NET (myeloperoxidase-DNA complexes) were analyzed in plasma from 4 cross-sectional SLE cohorts (n = 44–142), 1 longitudinal SLE cohort (n = 47), and healthy individuals (n = 100) using ELISA. Type I interferon activity was determined using a cell reporter system. RESULTS. Patients with SLE had elevated levels of NET in circulation compared to healthy controls (p < 0.01). NET levels identified patients with a severe disease phenotype characterized by IC-driven nephritis (p < 0.05). Though not associated with current disease activity (p = 0.20), levels of NET were associated with future increase in the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) within 3 months (OR 1.75, p = 0.01), as well as an overall heightened SLEDAI over 1 year (p < 0.01). Finally, levels of NET were associated with arterial events (OR 5.0, p = 0.02) and endothelial cell activation (p < 0.001). CONCLUSION. NET levels are elevated in patients with SLE, associated with IC-driven disease. NET levels provide significant clinical value in identifying patients at risk of active disease and/or severe disease, including nephritis and cardiovascular disease, and may allow for early interventions.